Respon Pertumbuhan dan Hasil Selada (Lactuca sativa L.) RZ Junction terhadap Variasi Ketinggian Talang pada Sistem Hidroponik NFT A-Frame - Kintan Kharisma Kintan Kharisma Putri; Ahmad Marzuki; Aulia Rahmawati (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Lettuce (Lactuca sativa L.) is a high-value horticultural crop whose production quality is closely linked to cultivation method. The NFT A-Frame hydroponic system maximizes planting density in limited land; however, differences in gutter height create microclimatic stratification—particularly in light intensity—that may affect plant growth and yield. This study aimed to determine the effect of gutter height variation on the growth and yield of RZ Junction lettuce. The research was conducted at Kebun Sayur 24, Bojongsari Village, Kebumen Regency, from June to July 2025, using a Completely Randomized Design with three treatments: K1 (lower gutter), K2 (middle gutter), and K3 (upper gutter), each replicated three times. Variables observed included plant height, leaf number, root length, stem diameter, and fresh weight. Data were analyzed using ANOVA at 95% confidence level, followed by the Least Significant Difference test at 5% significance. Results showed that gutter height significantly affected most growth parameters. K3 consistently produced the best performance at harvest (6 WAP): plant height (28.15 cm), leaf number (18.25 leaves), stem diameter (3.33 cm), and fresh weight without roots (159.33 g), while K1 recorded the lowest values due to cumulative shading effects from upper layers. Root length was the only parameter showing no consistent significant difference among treatments, indicating relatively uniform nutrient solution distribution across gutter levels. The upper gutter position (K3) is recommended for RZ Junction lettuce cultivation in the NFT A-Frame system to achieve optimal growth and yield